2017
DOI: 10.1371/journal.pone.0173712
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibitor chloroquine increases sensitivity to cisplatin in QBC939 cholangiocarcinoma cells by mitochondrial ROS

Abstract: The tumor cells have some metabolic characteristics of the original tissues, and the metabolism of the tumor cells is closely related to autophagy. However, the mechanism of autophagy and metabolism in chemotherapeutic drug resistance is still poorly understood. In this study, we investigated the role and mechanism of autophagy and glucose metabolism in chemotherapeutic drug resistance by using cholangiocarcinoma QBC939 cells with primary cisplatin resistance and hepatocellular carcinoma HepG2 cells. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 38 publications
5
72
0
Order By: Relevance
“…In accordance with these results, Qu et al 27 showed that CQ increases the sensitivity to cisplatin in cholangiocarcinoma cells by increasing ROS. Consequently, the cause of apoptosis induction in the combination treatment might be related to the increase in DNA damage and the accumulation of ROS.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In accordance with these results, Qu et al 27 showed that CQ increases the sensitivity to cisplatin in cholangiocarcinoma cells by increasing ROS. Consequently, the cause of apoptosis induction in the combination treatment might be related to the increase in DNA damage and the accumulation of ROS.…”
Section: Discussionmentioning
confidence: 56%
“…Consequently, the cause of apoptosis induction in the combination treatment might be related to the increase in DNA damage and the accumulation of ROS. In accordance with these results, Qu et al 27 showed that CQ increases the sensitivity to cisplatin in cholangiocarcinoma cells by increasing ROS. Also, Ganguli et al 28 found that inhibition of autophagy by CQ potentiates the anticancer properties of artemisinin by promoting ROS-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 56%
“…[13][14][15] This finding provides support for mitochondria as targets of cisplatin in HCC because these organelles are the major sites of ROS formation in the cell, 16,17 and the production of mitochondrial ROS (mtROS) is an important indicator of damaged mitochondrial antioxidant defence function. [13][14][15] This finding provides support for mitochondria as targets of cisplatin in HCC because these organelles are the major sites of ROS formation in the cell, 16,17 and the production of mitochondrial ROS (mtROS) is an important indicator of damaged mitochondrial antioxidant defence function.…”
Section: Introductionmentioning
confidence: 80%
“…This mechanism could be developed as a novel target for treatment of HCC in the future.This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.Several studies, including our own, have reported that cisplatin enhanced the reactive oxygen species (ROS) levels in HCC cells. [13][14][15] This finding provides support for mitochondria as targets of cisplatin in HCC because these organelles are the major sites of ROS formation in the cell, 16,17 and the production of mitochondrial ROS (mtROS) is an important indicator of damaged mitochondrial antioxidant defence function. 18 Furthermore, low mtROS levels can activate the mitophagy-lysosome pathway to degrade damaged mitochondria and mtROS.…”
mentioning
confidence: 80%
“…Blessing et al reported the importance of autophagy in the progression of PCa, demonstrated the mechanism of enhanced autophagy, and proposed that autophagy has potential for treating advanced PCa (Blessing et al 2017). Many studies have indicated that pharmacologically suppressing autophagy with agents such as chloroquine and metformin, as well as the agents described herein, could enhance the cell-killing effect of cancer therapeutic agents (Qu et al 2017;Yoshida 2017;Kotcherlakota et al 2018).…”
Section: Introductionmentioning
confidence: 97%